Do individuals' resist green home investment decisions? An empirical study from status quo bias and inertia perspective - R, Sharmila Devi; Perumandla, Swamy (Frontiers in Sustainable Cities, 2023)
Introduction The study explores the influence of Status Quo Bias theory constructs and the mediating role of inertia on individuals' resistance in making sustainable green home investment decisions among Indian homeowners and prospective homebuyers. Methods A structured questionnaire was administered to 404 participants, and data analysis was performed using Partial Least Squares Structured Equation Modeling (PLS SEM). Results The findings indicate that factors such as loss aversion, transition costs, adherence to social norms, and self-efficacy to change significantly contribute to individuals' resistance to green home investments. Inertia further amplifies the relationship between transition costs, social norms, and self-efficacy to change, but does not mediate the impact of loss aversion. Discussion This study is valuable for enhancing our understanding of biases in decision-making processes. To combat this resistance, it is crucial to provide clear information about the benefits of green home upgrades and offer incentives that reduce perceived costs and risks. This research sheds new light on the influence of status quo bias and inertia specifically within the context of green home investment decisions, addressing contemporary concerns for environmental sustainability and the increasing importance of such decisions in today's world.